A theorem of the alternative and a two-function minimax theorem - Anton Stefanescu (Journal of Applied Mathematics)
The two main results of the paper are a theorem of the alternative of Gordan type and a two-function minimax theorem. Both are based on some weakened convexlike properties, without any vector space structure.